Жаргонна лексика в заголовках інтернет-видання «Українська правда» - Навальна, Марина; Navalna, Maryna (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті схарактеризовано найуживаніші жаргонні лексеми із заголовків інтернет-видання «Українська правда», виявлено нові жаргонні одиниці,простежено розширення сфери функціонування кримінальних жаргонізмів у медійних матеріалах суспільно-політичної тематики.In the article described the most frequently used slangy lexemes from the titles of Internet edition «Ukrainska Pravda», detected the newslangy units, traced expansions of sphere of functioning slangs in media materials of socio-political subjects. There are the most widely represented criminal and youth slangs in publicistic material, which used to characterize the activity of Ukrainian politicians and political parties and blocs, preelection and electoral processes, defined negativism of social processes, etc. The research shows that slangs expanded sphere of theirs functioning, got new shades of meaning, that they go beyond of their traditional spoken use in social dialects and serve the means of expression of predominantly negative value and expressivity of newspaper’s text. Replenishment of publicistic texts caused by extralinguistic factors, in particular criminalization of Ukrainian society in various fields and on different levels.
Slangy Vocabulary in the Titles of Internet Edition «Ukrainska Pravda»
Keywords: літературний стандарт; жаргонізми; стилістична роль; сфера використання; емоційно-експресивне забарвлення; literary standard; slangs; stylistic role; sphere of using; emotional and expressive coloring